2020
DOI: 10.1212/nxi.0000000000000689
|View full text |Cite
|
Sign up to set email alerts
|

Complement factor I deficiency

Abstract: ObjectiveTo raise awareness of complement factor I (CFI) deficiency as a potentially treatable cause of severe cerebral inflammation.MethodsCase report with neuroradiology, neuropathology, and functional data describing the mutation with review of literature.ResultsWe present a case of acute, fulminant, destructive cerebral edema in a previously well 11-year-old, demonstrating massive activation of complement pathways on neuropathology and compound heterozygote status for 2 pathogenic mutations in CFI which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…8,9 The relapsing nature of this patient's disease process is curious and perhaps explained by the speculation that chronic alternative pathway activation caused by CFI deficiency is limited by the depletion of C3. 10,11 A surge of C3 can be induced by a stressor, such as viral illness. With this surge, the alternative pathway is no longer substrate limited and can mount a fulminant unchecked inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 The relapsing nature of this patient's disease process is curious and perhaps explained by the speculation that chronic alternative pathway activation caused by CFI deficiency is limited by the depletion of C3. 10,11 A surge of C3 can be induced by a stressor, such as viral illness. With this surge, the alternative pathway is no longer substrate limited and can mount a fulminant unchecked inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous partial CFI deficiency has been associated with autoinflammatory processes, which are a group of disorders often characterized by episodic inflammation driven by the innate immune system in the absence of pathogens, autoantibodies, or antigen specific T cells 8 . The relapsing nature of this patient's disease process is curious, and perhaps explained by the speculation that chronic alternative pathway activation caused by CFI deficiency is limited by depletion of C3 10,11 . A surge of C3 can be induced by a stressor, such as viral illness.…”
Section: Case Reportmentioning
confidence: 99%
“…We also found that ASD and control NPCs, neurons and astrocytes secreted and/or expressed CFB and CFD, key components of the alternative complement pathway, and CFH and CFI, inhibitors of the classic and alternative complement pathways [ 1 ]. Although abnormal expression of these complement components and regulators has been implicated in cerebral inflammation [ 34 ], degeneration [ 35 ] and retinopathies [ 36 , 37 ], the possible roles of these proteins in ASD and in the normal developing human nervous system are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that all ASD and control cell lines analyzed express CFH and CFI mRNA and secrete relatively high levels of CFH and CFI proteins, which are inhibitors of the classic and alternative pathways of the complement system. Whereas the expression of these complement components and regulators are implicated in cerebral in ammation [38], degeneration [39] and retinopathies [40,41], the physiological roles of these proteins in the developing human nervous system deserve further investigation. Finally, we observed constitutive expression and secretion of the critical component of both classical and lectin cascades C4 by ASD and control NPCs, neurons and astrocytes, and also constitutive secretion of C4b by ASD and control neurons and astrocytes.…”
Section: Discussionmentioning
confidence: 99%